Upaya Menanamkan Sikap Moderasi Beragama Melalui Pendidikan Agama Islam Pada Mahasiswa Perguruan Tinggi - Taklimudin, Taklimudin; Jannah, Nur (Belajea: Jurnal Pendidikan Islam, 2023)
Public university (PTU) students are usually very vulnerable to the ideas of extremism and radicalism that are starting to spread into the world of education, because they tend to see religious issues only from a black and white perspective. Efforts to instill and build an attitude of religious moderation through Islamic religious education (PAI) that students receive in tertiary institutions are very good in forming an attitude of religious moderation among students by providing education about the meaning of respecting the diversity of opinions of Muslims, including differences of opinion among students themselves. . The aim of this research is to describe and analyze Islamic religious education (PAI) efforts to instill values and attitudes of religious moderation among students. This research uses a qualitative approach and data collection techniques use observation, interviews and documentation methods. And the results obtained from this research show that Islamic Religious Education (PAI) instills and builds an attitude of religious moderation through the methodology of Islamic religious teachings, the Islamic Religious Education (PAI) curriculum which leads to personalities living in harmony, mutual respect, care and tolerance without having to This creates conflict because of existing differences, the example and attitude of lecturers, open discussion space, the Al-Qur’an Tutoring Program (BBQ), mentoring and coaching in student activity units and evaluations. Can build an attitude of religious moderation as an effort for students to respect religious diversity and build collective awareness of Public University (PTU) students.